The International Red Cross - Connolly, Sean, 1956- (London : Franklin Watts, 2008)
Describes the history of the International Red Cross and discusses its programs, such as education and disaster and war relief efforts.
Help in a crisis -- Born on a battlefield -- A special mission -- Structure of the Red Cross -- Conflicts and their aftermath -- Emergency action -- Working with others -- Closer to home -- Looking to the future -- How you can help.
Includes bibliographical references (p. 45) and index.
7.9
5-8
Keywords: Red Cross and Red Crescent -- Juvenile literature; Red Cross and Red Crescent; Disaster relief; Red Cross and Red Crescent